Using Microsoft Visio 2010 - Roth, Chris, 1968-; Safari eBooks ([Indianapolis, Ind.] : Que Pub., 2011)
"Get comfortable with Microsoft Visio 2010, the latest version of Microsoft Visio. Don't just read about it: see it and hear it with step-by-step video tutorials and valuable audio sidebars ..."--Resource description page.
Title from resource description page (viewed Aug. 19, 2011).
Keywords: Computer graphics; Microsoft Visio; Electronic books